Cellular Uptake: Theoretical and Computational Investigations of Nanoparticle–Biomembrane Interactions in Cellular Delivery (Small 9‐10/2015). Issue 9 (March 2015) - Ding, Hong‐ming; Ma, Yu‐qiang
Abstract : Nanoparticles have recently been widely applied in biomedicine. Understanding how nanoparticles interact with biosystems (especially cells) is crucial for their further biomedical application. On page 1055, H.‐m. Ding and Y.‐q. Ma summarize the current progress on theoretical and computational investigations of nanoparticle‐biomembrane interactions in cellular delivery. The parameters that determine the cellular uptake and subsequent intracellular trafficking of nanoparticles are discussed in detail.